LC-MS Analysis of Ethyl Acetate Fraction of Gandaria (Bouea macrophylla Griff.) Stem Bark and Molecular Docking Study against HER2 Protein - Junia Salsha Primawati; Sriwijayanti Sriwijayanti; Boima Situmeang; Siti Safuroh; Yuke Agustin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Breast cancer is a disease that has long been a source of concern for the public due to its high mortality rate. Excessive exposure to free radicals has been identified as a potential carcinogen, thus necessitating the utilization of antioxidants to counteract the damaging effects of these molecules. Gandaria (Bouea macrophylla Griff.) is a plant that is commonly found in Java, Sumatra, Maluku, and Kalimantan. B. macrophylla is known to have strong antioxidant activity, which is correlated with anticancer activity. A part of B. macrophylla that has not been extensively researched is its stem bark. The objective of this study was to analyze the potential of the ethyl acetate fraction of B. macrophylla stem bark as an anticancer agent using in silico method. The ethyl acetate fraction of B. macrophylla stem bark was characterized by LC-MS, which revealed four major compounds: 4-hydroxy-3-(3-oxo-1-phenylbutyl)-chromen-2-one, 1-(2,5-dihydroxyphenyl)-propan-1-one, 3-ethoxy-4-hydroxybenzaldehyde, and 2-nitrobenzoic acid. Molecular docking was performed between the compounds against the HER2 protein with PDB ID 3RCD. The four compounds demonstrated binding energy values of -8.29 kcal/mol, -5.04 kcal/mol, -4.66 kcal/mol, and -4.28 kcal/mol, respectively.